Loss of HNF6 expression correlates with human pancreatic cancer progression - Pekala, Kelly R. (2014)
Normal pancreatic epithelium progresses through various stages of pancreatic intraepithelial neoplasms (PanINs) in the development of pancreatic ductal adenocarcinoma (PDAC). Transcriptional regulation of this progression is poorly understood. In mouse, the Hnf6 transcription factor is expressed in ductal cells and at lower levels in acinar cells of the adult pancreas, but not in mature endocrine cells. Hnf6 is critical for terminal differentiation of the ductal epithelium during embryonic development and for pancreatic endocrine cell specification. We previously showed that, in mice, loss of Hnf6 from the pancreatic epithelium during organogenesis results in increased duct proliferation and altered duct architecture, increased periductal fibrosis and acinar-to-ductal metaplasia. Here we show that decreased expression of HNF6 is strongly correlated with increased severity of PanIN lesions in samples of human pancreata and is absent from >90% of PDAC. Mouse models in which cancer progression can be analyzed from the earliest stages that are seldom accessible in humans support a role for Hnf6 loss in progression from early to late stage PanIN and PDAC. In addition, gene expression analyses of human pancreatic cancer reveal decreased expression of HNF6 and its direct and indirect target genes compared to normal tissue and up-regulation of genes that act in opposition to HNF6 and its targets. The negative correlation between HNF6 expression and pancreatic cancer progression suggests that HNF6 maintains pancreatic epithelial homeostasis in humans, and that its loss contributes to the progression from PanIN to ductal adenocarcinoma. Insight on the role of HNF6 in pancreatic cancer development could lead to its use as a biomarker for early detection and prognosis.